2019
DOI: 10.1128/jvi.01887-18
|View full text |Cite
|
Sign up to set email alerts
|

Infection and Functional Modulation of Human Monocytes and Macrophages by Varicella-Zoster Virus

Abstract: Varicella-zoster virus (VZV) is associated with viremia during primary infection that is presumed to stem from infection of circulating immune cells. While VZV has been shown to be capable of infecting a number of different subsets of circulating immune cells, such as T cells, dendritic cells, and NK cells, less is known about the interaction between VZV and monocytes. Here, we demonstrate that blood-derived human monocytes are permissive to VZV replication in vitro. VZV-infected monocytes exhibited each tempo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 57 publications
2
32
0
Order By: Relevance
“…This work was corroborated by a report demonstrating VZV infection of monocytes, NKT cells and B lymphocytes (150) and by productive infection of a THP-1 monocytic cell line (89). Although evidence suggesting monocyte differentiation to macrophage may be influenced by VZV infection in vivo, macrophage infection in vitro has previously been observed (56,148). As such, it is likely that although monocytes and macrophages represent a dynamic axis for the induction and maintenance of anti-viral states, VZV is able to counteract this effective branch of the innate immune system through direct infection and immune evasion strategies.…”
Section: Vzv Infection and Manipulation Of Monocytes And Macrophagessupporting
confidence: 78%
See 2 more Smart Citations
“…This work was corroborated by a report demonstrating VZV infection of monocytes, NKT cells and B lymphocytes (150) and by productive infection of a THP-1 monocytic cell line (89). Although evidence suggesting monocyte differentiation to macrophage may be influenced by VZV infection in vivo, macrophage infection in vitro has previously been observed (56,148). As such, it is likely that although monocytes and macrophages represent a dynamic axis for the induction and maintenance of anti-viral states, VZV is able to counteract this effective branch of the innate immune system through direct infection and immune evasion strategies.…”
Section: Vzv Infection and Manipulation Of Monocytes And Macrophagessupporting
confidence: 78%
“…More recently however, our laboratory performed an investigation into the susceptibility of human monocytes and macrophages to VZV infection. We reported productive VZV infection of both freshly isolated human monocytes and differentiated macrophages (56). Interestingly, macrophages were highly permissive to VZV infection.…”
Section: Vzv Infection and Manipulation Of Monocytes And Macrophagesmentioning
confidence: 95%
See 1 more Smart Citation
“…CD14 + monocytes were derived from healthy human blood as described previously . Briefly, peripheral blood mononuclear cells from healthy volunteers at China‐Japan Friendship Hospital were isolated by gradient centrifugation with Ficoll‐Paque (GE Healthcare Bio‐Science).…”
Section: Methodsmentioning
confidence: 99%
“…Mononuclear cells: Infection of the immune cells by VZV results in attenuation of the antiviral mechanisms to control the infection and limit spread of the virus [320]. Several studies have shown that VZV productively infects human peripheral blood mononuclear cells (PBMNCs) and the infected PBMNCs then disseminate the virus to distal organs to produce clinical disease [320][321][322][323][324]. VZV induces an IFNmediated Th1 reaction in PBMNCs.…”
Section: T-lymphocytes: T-cell Mediated Immunity Consists Of Cd4 and mentioning
confidence: 99%